2004
DOI: 10.1038/sj.bjc.6601968
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A8 overexpression in transitional cell carcinoma of the bladder: identification of two tumour-associated antigen peptides

Abstract: Bladder carcinoma is the fourth most common cancer in men and the eighth most common cancer among women. Our study is aimed to characterise tumour-associated antigen peptides of transitional cell carcinoma of the bladder (TCC). A DNA micro-arraybased differential display analysis of 10 000 genes was carried out, and MAGE-A8 gene expression was detected in the tumour, and not in the normal bladder. High occurrence of MAGE-A8 expression was observed in fresh tumour samples (17 out of 23) and TCC lines (four of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The HHD mouse combines classic HLA transgenesis (HLA-A2.1/D b -h2m single chain) with selective destruction of murine H-2 (double knockout deletion of the murine h2m and D b genes) that restricts the whole class I-derived T-cell repertoire to HLA-A2.1. Others and we have identified several HLA-A2.1-restricted epitopes from TAAs, such as MUC1 (21), BA46 (22), PTH-rP (30), HER-2/neu and hTERT (31), and MAGE-A8 (32). PAP, PSA, PSMA, and STEAP were found to be overexpressed in prostate cancer versus BPH samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The HHD mouse combines classic HLA transgenesis (HLA-A2.1/D b -h2m single chain) with selective destruction of murine H-2 (double knockout deletion of the murine h2m and D b genes) that restricts the whole class I-derived T-cell repertoire to HLA-A2.1. Others and we have identified several HLA-A2.1-restricted epitopes from TAAs, such as MUC1 (21), BA46 (22), PTH-rP (30), HER-2/neu and hTERT (31), and MAGE-A8 (32). PAP, PSA, PSMA, and STEAP were found to be overexpressed in prostate cancer versus BPH samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antigens that are uniquely expressed in tumours (Luftl et al, 2004); antigens derived from differentiation markers (Panelli et al, 2000); antigens arise from mutations that are common in tumours (McArdle et al, 2000); antigens from a viral source (Youde et al, 2004); and selfantigens that are overexpressed in tumours (Bar-Haim et al, 2004). In the latter category, although strong immune reactions against this type of antigens might result in the destruction of normal tissues, experience with peptide immunisation has not demonstrated high toxicity in humans and animals (Gross et al, 2004).…”
mentioning
confidence: 99%
“…8 More recently, Bar-Haim et al reported the overexpression of MAGE-A8 mRNA in 70% of bladder tumours. 9 In our previous analysis, 7 we observed that only half of tumours expressing MAGE-A mRNAs were positive on Western blot with mAb 57B, a mAb that cross reacts with MAGE-A1, -A2, -A3, -A4, -A6 and -A12 antigens. 10,11 We made a similar observation using the bladder cancer cell line RT4, which strongly expressed MAGE-A transcripts but was negative with mAb 57B.…”
mentioning
confidence: 99%